Positive electrode lead paste of lead storage battery and preparation method of positive electrode lead paste

By using rare earth-carbon-based composite additives and high-temperature curing technology, a stable three-dimensional conductive network is formed, which solves the problems of poor conductivity and low utilization rate of active materials in the positive electrode of lead-acid batteries, thereby improving the cycle life and charging efficiency of lead-acid batteries.

CN121035202AActive Publication Date: 2025-11-28TIANNENG BATTERY GROUP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202511051010.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-29
Publication Date
2025-11-28
Estimated Expiration
2045-07-29

AI Technical Summary

Technical Problem

Existing lead-acid batteries suffer from problems such as poor conductivity, uneven reaction, low utilization of active materials, and short cycle life, resulting in performance bottlenecks.

Method used

The rare earth-carbon based composite lead-acid battery cathode additive formula includes a multidimensional conductive network composed of carbon nanotubes, graphene, expanded graphite, SnO2-rare earth mixture, nano red lead powder, sodium perborate and sulfonated polyaniline. A stable three-dimensional conductive structure is formed through ball milling and emulsification treatment. Combined with high temperature curing technology, the utilization rate of active materials and battery performance are improved.

Benefits of technology

This invention realizes a multi-dimensional conductive path for the positive electrode of lead-acid batteries, improves the utilization rate of active materials, extends the cycle life of batteries, and enhances charging efficiency and low-temperature performance.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides a lead storage battery positive electrode lead paste and a preparation method thereof. The invention provides a rare earth-carbon-based composite lead storage battery positive electrode additive formula which comprises the following components in parts by weight: 25-35 parts of a carbon material, the carbon material comprises a carbon nanotube, graphene and expanded graphite, and the mass ratio of the carbon nanotube to the graphene to the expanded graphite is 1: 2: 3; 20 to 30 parts of a binder; the rare earth comprises a Ce element, and the molar ratio of the Ce element to the Sn element is 1: (8-10); 30 to 40 parts of a 4BS seed crystal; 50 to 80 parts of nano red lead powder; 1 to 1.5 parts of polyester fiber; and 5-10 parts of sodium perborate. According to the invention, a multi-dimensional conductive network is constructed through the combination of the carbon nanotubes, the graphene, the expanded graphite and the conductive binder, a stable three-dimensional network is formed, the problem of conductive anisotropy of traditional lead paste is solved, heterojunctions are formed through the SnO2-rare earth mixture, oxygen evolution overpotential is reduced, grains are refined, and corrosion of a positive grid is inhibited.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of lead storage batteries, in particular to a positive lead paste of a lead storage battery and a preparation method thereof. BACKGROUND

[0002] Lead storage batteries are widely used due to their low cost and high safety, but the performance bottleneck of the positive electrode is significant:

[0003] Low utilization rate of active material: limited by poor electrical conductivity and ion diffusion resistance, only about 50% of the active material participates in the reaction.

[0004] Short cycle life: active material softening and falling off leads to rapid capacity decay, especially when deeply discharged (DOD>50%).

[0005] Poor low-temperature performance: the viscosity of the electrolyte increases at low temperatures, ion transport is blocked, and the discharge capacity drops sharply.

[0006] Therefore, it is particularly important to improve the positive electrode of the lead storage battery.

[0007] For example, the patent application with publication number CN117855467A discloses a positive lead paste for a lead storage battery, which includes lead powder and additives. The additives include calcium peroxide 0.3% to 2%, expanded graphite 0.2% to 0.3%, graphene 0.05% to 0.1%, four-base lead sulfate 0.8% to 1%, metal sulfate 0.1% to 0.3%, and polyester short fiber 0.1% to 0.15%, by mass of the positive lead paste. A 4BS skeleton structure is formed by high-temperature curing, and the decomposition of calcium peroxide promotes the oxidation of free lead, improving the bonding force of active materials. This scheme can improve the cycle life of the product by 15%, but does not solve the problem of anisotropic electrical conductivity, and the decomposition rate of calcium peroxide is difficult to control.

[0008] For example, the patent application with publication number CN118472190A discloses a positive lead paste for a high-capacity long-life storage battery, which includes lead powder, dilute sulfuric acid, water, and additives. The additives include sodium perborate 1 to 3 parts, 4BS 0.5 to 2 parts, antimony trioxide 1 to 3 parts, tin pyrophosphate 1 to 3 parts, polyolefin 2 to 4 parts, conductive carbon material 2 to 4 parts, and polyester short fiber 1 to 1.5 parts, by mass of 1000 parts of lead powder. The conductive carbon material is at least one of acetylene black, graphite, graphene, fullerene, and carbon nanotubes. However, the added graphene, carbon nanotubes, and expanded graphite carbon materials are prone to agglomeration, and the structure is prone to collapse.

[0009] In summary, the existing technology still has the following three major shortcomings:

[0010] (1) The conductive network of traditional carbon materials (such as graphite) is a two-dimensional or partially three-dimensional structure, which cannot penetrate the internal pores of lead paste, resulting in the break of electron transport path and the limited reaction area of ​​active material.

[0011] (2) The traditional curing temperature fluctuation (70-85℃) leads to large size differences in 4BS whiskers (length-to-diameter ratio <10:1) and a porosity of only about 40%, resulting in uneven electrolyte penetration, increased polarization, and decreased charging efficiency.

[0012] (3) SnO2 alone has limited catalytic activity and cannot effectively reduce the oxygen evolution energy barrier (the traditional scheme Δη≥200mV), which leads to increased water decomposition during charging and increased grid corrosion rate. Summary of the Invention

[0013] To address the aforementioned technical problems in the existing technology, this invention provides a lead-acid battery positive electrode paste and its preparation method.

[0014] This invention provides a rare earth-carbon-based composite lead-acid battery cathode additive formulation, comprising, by weight:

[0015] 25-35 parts of carbon material, wherein the carbon material includes carbon nanotubes, graphene and expanded graphite;

[0016] 20-30 parts of adhesive;

[0017] 8 to 12 parts of SnO2-rare earth mixture, wherein rare earth includes Ce element, and the molar ratio of Ce element to Sn element is 1:8 to 10;

[0018] 30-40 parts of 4BS seed crystals;

[0019] 50-80 parts of nano red lead powder;

[0020] 1 to 1.5 parts polyester fiber;

[0021] Sodium perborate, 5-10 parts.

[0022] Preferably, the binder is sulfonated polyaniline. Sulfonated polyaniline is hydrophilic, allowing for better and more uniform mixing in the lead paste. As a conductive agent, sulfonated polyaniline has high adsorption capacity, effectively adsorbing the electrolyte and thus improving the contact and penetration of the sulfuric acid electrolyte into the active material of the electrode plates, relatively increasing the utilization rate of the active material. Furthermore, it can increase the porosity of the active material, thereby improving the initial capacity and charge acceptance of the battery.

[0023] Preferably, the mass ratio of the carbon nanotubes, graphene, and expanded graphite is 1:2:3.

[0024] Preferably, the SnO2-rare earth mixture is a mixture of SnO2 and rare earth elements or a mixture of SnO2 and rare earth oxides.

[0025] The present invention also provides a method for preparing lead-acid battery positive electrode paste, wherein the raw materials for preparing lead-acid battery positive electrode paste include lead powder, dilute sulfuric acid, water and each material in the above-mentioned rare earth-carbon based composite lead-acid battery positive electrode additive formula.

[0026] The mass ratio of lead powder and carbon material in the rare earth-carbon-based composite lead-acid battery cathode additive formulation is 1000:25-35;

[0027] The preparation method includes the following steps:

[0028] (1) The red lead powder, 4BS seed crystals and SnO2-rare earth mixture of the formula amount were ball-milled and mixed in an inert gas atmosphere, and the nano-sized powder was obtained by sieving to prepare pre-additive A.

[0029] (2) Mix and emulsify the carbon material, binder and water in the specified amounts to obtain emulsion B;

[0030] (3) Dry mix the lead powder, sodium perborate, polyester fiber and pre-made additive A according to the formula, then add emulsion B and water, mix evenly, then add dilute sulfuric acid, mix evenly and then make paste.

[0031] Preferably, in the raw materials for preparing the positive electrode lead paste for lead-acid batteries, by mass parts, every 1000 parts of lead powder corresponds to 90-105 parts of dilute sulfuric acid, and every 1000 parts of lead powder corresponds to 110-130 parts of water.

[0032] Preferably, in step (1), the ball milling is carried out in a ball mill, and hard grinding balls are also added to the ball mill. The mass ratio of the hard grinding balls to the added raw materials is 10:1. The rotation speed of the ball mill is 500-1000 rpm, and the ball milling time is 20-30 hours. The sieve used for sieving has a sieve aperture of 60 nm. The red lead powder, 4BS seed crystals, and SnO2-rare earth mixture are ball-milled to a particle size ≤60 nm to improve the interfacial reaction activity.

[0033] Preferably, in step (2), an ultrasonic emulsifier is used for mixing and emulsification. The shearing speed of the ultrasonic emulsifier during mixing and emulsification is 2500-3000 r / min, and the mixing and emulsification time is 45-60 min.

[0034] Preferably, in step (3), the paste discharge temperature is not higher than 45°C.

[0035] The present invention also provides a lead-acid battery positive electrode paste, which is prepared by the above-mentioned method for preparing lead-acid battery positive electrode paste.

[0036] The present invention also provides a lead-acid battery, including a positive electrode plate, wherein the positive electrode plate is prepared by coating the positive electrode lead paste of the above-mentioned lead-acid battery onto the positive electrode plate grid and then curing it at high temperature. The high temperature curing temperature is 75-80°C, the time is 8-10 hours, and the ambient humidity is controlled within the range of 90%-95% relative humidity (RH).

[0037] Compared with the prior art, the present invention has the following beneficial effects:

[0038] (1) A multidimensional conductive network is constructed by combining carbon nanotubes (1D) + graphene (2D) + expanded graphite (3D) + conductive binder. Expanded graphite fills the gaps between graphene sheets, and the conductive bonding effect of the binder forms a stable three-dimensional network. Carbon nanotubes act as “wires” to connect graphene sheets, and expanded graphite provides pore support, solving the problem of anisotropy in conductivity of traditional lead paste and forming an omnidirectional conductive path.

[0039] (2) The SnO2-rare earth mixture forms a heterojunction, which reduces the oxygen evolution overpotential, refines the grains, inhibits the corrosion of the positive electrode grid, reduces the decomposition of water during the charging process, improves the charging efficiency, and extends the electrode life.

[0040] (3) Sodium perborate can improve the bonding force between the grid and the active material, prevent the active material of the plate from falling off, and sodium perborate will decompose in humid air or when slightly heated and release oxygen. Combined with 4BS seed crystals to guide the growth of three-dimensional whisker structure, it is conducive to the formation of PbO, reduces the content of free lead, and thus improves the performance of lead-acid battery. Detailed Implementation

[0041] Example 1

[0042] 1. Nano-scale pretreatment of additive component A:

[0043] (1) Add 50 parts of red lead powder, 30 parts of 4BS seed crystals and 8 parts of SnO2-rare earth mixture (SnO2-rare earth mixture is a mixture of SnO2 and Ce elements, wherein the molar ratio of Ce to Sn is 1:8) into a high-energy ball mill. Load hard grinding balls (zirconia and tungsten carbide in a mass ratio of 1:1) into the ball mill jar. The mass ratio of the added powder to the hard grinding balls is 1:10.

[0044] (2) Inert gas—argon—is introduced into the ball mill jar to prevent the powder material from being oxidized during the grinding process.

[0045] (3) Set the rotation speed (500 rpm) and grinding time (20 hours), and run intermittently to avoid overheating.

[0046] (4) After grinding, the grinding balls are separated by sieving, and the nano powder is sieved at the same time (sieve aperture is 60nm) to obtain pretreated nano-level additive A.

[0047] 2. Additive B component water emulsification treatment

[0048] Add 25 parts of composite carbon material (carbon nanotubes: graphene: expanded graphite mass ratio = 1:2:3) and 40 parts of deionized water to an ultrasonic emulsifier. Stir at low speed for 30 minutes to fully wet the material. Then add 20 parts of sulfonated polyaniline binder (supplier: Shanghai Chuangsai Technology Co., Ltd.; product name: polyaniline, 98%, sulfonic acid doped; the same below). Increase the shear speed of the emulsifier to 2500 r / min and emulsify for 45 minutes to obtain emulsion B.

[0049] 3. Lead paste preparation process

[0050] Add 1000 parts lead powder, 5 parts sodium perborate, 1 part polyester fiber, and premixed additive A to the paste mixer and start the dry mixing machine for 5 minutes. Then, spray the pretreated additive component B into the agitated lead paste in the paste mixer in a mist form over 5 minutes. Next, pour in 70 parts deionized water over 3 minutes, and continue stirring for 5 minutes after the addition is complete. Then, pour in 90 parts dilute sulfuric acid over 8 minutes, and continue stirring for 10 minutes after the addition is complete. Stop the machine when the temperature drops below 45 degrees Celsius.

[0051] 4. The electrode plate adopts high-temperature curing technology. The high-temperature curing stage is at 75℃ for 8 hours and 90%RH. This ensures that sodium perborate decomposes when heated to produce oxygen, which promotes grid oxidation and further oxidation of free lead in lead paste.

[0052] Example 2

[0053] 1. Nano-scale pretreatment of additive component A:

[0054] (1) Add 50 parts of red lead powder, 30 parts of 4BS seed crystals and 8 parts of SnO2-rare earth mixture (SnO2-rare earth mixture is a mixture of SnO2 and Ce element, wherein the molar ratio of Ce element to Sn element is 1:9) into a high-energy ball mill. Load hard grinding balls (zirconia and tungsten carbide in a mass ratio of 1:1) into the ball mill jar. The mass ratio of the added powder material to the hard grinding balls is 1:10.

[0055] (2) Inert gas—argon—is introduced into the ball mill jar to prevent the powder material from being oxidized during the grinding process.

[0056] (3) Set the rotation speed (500 rpm) and grinding time (20 hours), and run intermittently to avoid overheating.

[0057] (4) After grinding, the grinding balls are separated by sieving, and the nano powder is sieved at the same time (sieve aperture is 60nm) to obtain pretreated nano-level additive A.

[0058] 2. Additive B component water emulsification treatment

[0059] Add 25 parts of composite carbon material (carbon nanotubes: graphene: expanded graphite mass ratio = 1:2:3) and 40 parts of deionized water to an ultrasonic emulsifier, stir at low speed for 30 minutes to fully wet the material, then add 20 parts of sulfonated polyaniline binder, increase the shear speed of the emulsifier to 2500 r / min, and emulsify for 45 minutes to obtain emulsion B.

[0060] 3. Lead paste preparation process

[0061] Add 1000 parts lead powder, 5 parts sodium perborate, 1 part polyester fiber, and premixed additive A to the paste mixer and start the dry mixing machine for 5 minutes. Then, spray the pretreated additive component B into the agitated lead paste in the paste mixer in a mist form over 5 minutes. Next, pour in 70 parts deionized water over 3 minutes, and continue stirring for 5 minutes after the addition is complete. Then, pour in 90 parts dilute sulfuric acid over 8 minutes, and continue stirring for 10 minutes after the addition is complete. Stop the machine when the temperature drops below 45 degrees Celsius.

[0062] 4. The electrode plate adopts high-temperature curing technology. The high-temperature curing stage is at 75℃ for 8 hours and 90%RH. This ensures that sodium perborate decomposes when heated to produce oxygen, which promotes grid oxidation and further oxidation of free lead in lead paste.

[0063] Example 3

[0064] 1. Nano-scale pretreatment of additive component A:

[0065] (1) Add 50 parts of red lead powder, 30 parts of 4BS seed crystals and 8 parts of SnO2-rare earth mixture (SnO2-rare earth mixture is a mixture of SnO2 and Ce elements, wherein the molar ratio of Ce to Sn is 1:10) into a high-energy ball mill. Load hard grinding balls (zirconia and tungsten carbide in a mass ratio of 1:1) into the ball mill jar. The mass ratio of the added powder to the hard grinding balls is 1:10.

[0066] (2) Inert gas—argon—is introduced into the ball mill jar to prevent the powder material from being oxidized during the grinding process.

[0067] (3) Set the rotation speed (500 rpm) and grinding time (20 hours), and run intermittently to avoid overheating.

[0068] (4) After grinding, the grinding balls are separated by sieving, and the nano powder is sieved at the same time (sieve aperture is 60nm) to obtain pretreated nano-level additive A.

[0069] 2. Additive B component water emulsification treatment

[0070] Add 25 parts of composite carbon material (carbon nanotubes: graphene: expanded graphite mass ratio = 1:2:3) and 40 parts of deionized water to an ultrasonic emulsifier, stir at low speed for 30 minutes to fully wet the material, then add 20 parts of sulfonated polyaniline binder, increase the shear speed of the emulsifier to 2500 r / min, and emulsify for 45 minutes to obtain emulsion B.

[0071] 3. Lead paste preparation process

[0072] Add 1000 parts lead powder, 5 parts sodium perborate, 1 part polyester fiber, and premixed additive A to the paste mixer and start the dry mixing machine for 5 minutes. Then, spray the pretreated additive component B into the agitated lead paste in the paste mixer in a mist form over 5 minutes. Next, pour in 70 parts deionized water over 3 minutes, and continue stirring for 5 minutes after the addition is complete. Then, pour in 90 parts dilute sulfuric acid over 8 minutes, and continue stirring for 10 minutes after the addition is complete. Stop the machine when the temperature drops below 45 degrees Celsius.

[0073] 4. The electrode plate adopts high-temperature curing technology. The high-temperature curing stage is at 75℃ for 8 hours and 90%RH. This ensures that sodium perborate decomposes when heated to produce oxygen, which promotes grid oxidation and further oxidation of free lead in lead paste.

[0074] Example 4

[0075] 1. Nano-scale pretreatment of additive component A:

[0076] (1) Add 70 parts of red lead powder, 35 parts of 4BS seed crystals, and 10 parts of SnO2-rare earth mixture (SnO2-rare earth mixture is a mixture of SnO2 and Ce elements, wherein the molar ratio of Ce to Sn is 1:9) into a high-energy ball mill. Load hard grinding balls (zirconia and tungsten carbide in a mass ratio of 1:1) into the ball mill jar. The mass ratio of the added powder to the hard grinding balls is 1:10.

[0077] (2) Inert gas—argon—is introduced into the ball mill jar to prevent the powder material from being oxidized during the grinding process.

[0078] (3) Set the rotation speed (800 rpm) and grinding time (25 hours), and run intermittently to avoid overheating.

[0079] (4) After grinding, the grinding balls are separated by sieving, and the nano powder is sieved at the same time (sieve aperture is 60nm) to obtain pretreated nano-level additive A.

[0080] 2. Additive B component water emulsification treatment

[0081] Add 30 parts of composite carbon material (carbon nanotubes: graphene: expanded graphite mass ratio = 1:2:3) and 40 parts of deionized water to an ultrasonic emulsifier, stir at low speed for 30 minutes to fully wet the material, then add 25 parts of sulfonated polyaniline binder, increase the shear speed of the emulsifier to 2800 r / min, and emulsify for 50 minutes to obtain emulsion B.

[0082] 3. Lead paste preparation process

[0083] Add 1000 parts lead powder, 8 parts sodium perborate, 1.3 parts polyester fiber, and premixed additive A to the paste mixer and start the dry mixing machine for 5 minutes. Then, spray the pretreated additive component B into the agitated lead paste in the paste mixer over 5 minutes. Next, pour in 80 parts deionized water over 3 minutes, and continue stirring for 5 minutes after the addition is complete. Then, pour in 100 parts dilute sulfuric acid over 9 minutes, and continue stirring for 13 minutes after the addition is complete. Stop the machine when the temperature drops below 45 degrees Celsius.

[0084] 4. The electrode plate adopts high-temperature curing technology. The high-temperature curing stage is at 78℃ for 9 hours and 93%RH. This ensures that sodium perborate decomposes when heated to produce oxygen, which promotes grid oxidation and further oxidation of free lead in lead paste.

[0085] Example 5

[0086] 1. Nano-scale pretreatment of additive component A:

[0087] (1) Add 80 parts of red lead powder, 40 parts of 4BS seed crystals, and 12 parts of SnO2-rare earth mixture (SnO2-rare earth mixture is a mixture of SnO2 and Ce elements, wherein the molar ratio of Ce to Sn is 1:9) into a high-energy ball mill. Load hard grinding balls (zirconia and tungsten carbide in a mass ratio of 1:1) into the ball mill jar. The mass ratio of the added powder to the hard grinding balls is 1:10.

[0088] (2) Inert gas—argon—is introduced into the ball mill jar to prevent the powder material from being oxidized during the grinding process.

[0089] (3) Set the rotation speed (1000rpm) and grinding time (30 hours), and run intermittently to avoid overheating.

[0090] (4) After grinding, the grinding balls are separated by sieving, and the nano powder is sieved at the same time (sieve aperture is 60nm) to obtain pretreated nano-level additive A.

[0091] 2. Additive B component water emulsification treatment

[0092] Add 35 parts of composite carbon material (carbon nanotubes: graphene: expanded graphite mass ratio = 1:2:3) and 40 parts of deionized water to an ultrasonic emulsifier, stir at low speed for 30 minutes to fully wet the material, then add 30 parts of sulfonated polyaniline binder, increase the shear speed of the emulsifier to 3000 r / min, and emulsify for 60 minutes to obtain emulsion B.

[0093] 3. Lead paste preparation process

[0094] Add 1000 parts lead powder, 10 parts sodium perborate, 1.5 parts polyester fiber, and premixed additive A to the paste mixer and start the dry mixing machine for 5 minutes. Then, spray the pretreated additive component B into the agitated lead paste in the paste mixer in a mist form over 5 minutes. Next, pour in 90 parts deionized water over 3 minutes, and continue stirring for 5 minutes after the addition is complete. Then, pour in 105 parts dilute sulfuric acid over 10 minutes, and continue stirring for 15 minutes after the addition is complete. Stop the machine when the temperature drops below 45 degrees Celsius.

[0095] 4. The electrode plate adopts high-temperature curing technology. The high-temperature curing stage is at 80℃ for 10 hours and 95%RH. This ensures that sodium perborate decomposes when heated to produce oxygen, which promotes grid oxidation and further oxidation of free lead in lead paste.

[0096] Comparative Example 1

[0097] 1. Nano-scale pretreatment of additive component A:

[0098] (1) Add 70 parts of red lead powder and 35 parts of 4BS seed crystals into a high-energy ball mill. Load hard grinding balls (zirconia and tungsten carbide in a mass ratio of 1:1) into the ball mill jar. The mass ratio of the added powder to the hard grinding balls is 1:10.

[0099] (2) Inert gas—argon—is introduced into the ball mill jar to prevent the powder material from being oxidized during the grinding process.

[0100] (3) Set the rotation speed (800 rpm) and grinding time (25 hours), and run intermittently to avoid overheating.

[0101] (4) After grinding, the grinding balls are separated by sieving, and the nano powder is sieved at the same time (sieve aperture 60nm) to obtain pretreated nano-level additive A.

[0102] 2. Lead paste preparation process

[0103] Add 1000 parts lead powder, 8 parts sodium perborate, 1.3 parts polyester fiber, and premixed additive A to the paste mixing machine, and start the dry mixing machine for 5 minutes. Then, pour in 120 parts deionized water over 3 minutes, and continue mixing for 5 minutes after the addition is complete. Next, pour in 100 parts dilute sulfuric acid over 9 minutes, and continue mixing for 13 minutes after the addition is complete. Stop the machine when the temperature drops below 45 degrees Celsius. 3. The electrode plate adopts high-temperature curing technology. The high-temperature curing stage is at 78 degrees Celsius for 9 hours and 93% RH to ensure that sodium perborate decomposes upon heating to generate oxygen, promoting grid oxidation and further oxidation of free lead in the lead paste.

[0104] Comparative Example 2

[0105] 1. Nano-scale pretreatment of additive component A:

[0106] (1) Add 70 parts of red lead powder and 35 parts of 4BS seed crystals into a high-energy ball mill. Load hard grinding balls (zirconia and tungsten carbide in a mass ratio of 1:1) into the ball mill jar. The mass ratio of the added powder to the hard grinding balls is 1:10.

[0107] (2) Inert gas—argon—is introduced into the ball mill jar to prevent the powder material from being oxidized during the grinding process.

[0108] (3) Set the rotation speed (800 rpm) and grinding time (25 hours), and run intermittently to avoid overheating.

[0109] (4) After grinding, the grinding balls are separated by sieving, and the nano powder is sieved at the same time (sieve aperture is 60nm) to obtain pretreated nano-level additive A.

[0110] 2. Additive B component water emulsification treatment

[0111] Add 30 parts of composite carbon material (carbon nanotubes: graphene: expanded graphite mass ratio = 1:2:3) and 40 parts of deionized water to an ultrasonic emulsifier, stir at low speed for 30 minutes to fully wet the material, then add 25 parts of sulfonated polyaniline binder, increase the shear speed of the emulsifier to 2800 r / min, and emulsify for 50 minutes to obtain emulsion B.

[0112] 3. Lead paste preparation process

[0113] Add 1000 parts lead powder, 8 parts sodium perborate, 1.3 parts polyester fiber, and premixed additive A to the paste mixer and start the dry mixing machine for 5 minutes. Then, spray the pretreated additive component B into the agitated lead paste in the paste mixer over 5 minutes. Next, pour in 80 parts deionized water over 3 minutes, and continue stirring for 5 minutes after the addition is complete. Then, pour in 100 parts dilute sulfuric acid over 9 minutes, and continue stirring for 13 minutes after the addition is complete. Stop the machine when the temperature drops below 45 degrees Celsius.

[0114] 4. The electrode plate adopts high-temperature curing technology. The high-temperature curing stage is at 78℃ for 9 hours and 93%RH. This ensures that sodium perborate decomposes when heated to produce oxygen, which promotes grid oxidation and further oxidation of free lead in lead paste.

[0115] Comparative Example 3

[0116] 1. Nano-scale pretreatment of additive component A:

[0117] (1) Add 70 parts of red lead powder, 35 parts of 4BS seed crystals and 10 parts of SnO2-rare earth mixture into a high-energy ball mill. Load hard grinding balls (zirconia and tungsten carbide in a mass ratio of 1:1) into the ball mill jar. The mass ratio of the added powder to the hard grinding balls is 1:10.

[0118] (2) Inert gas—argon—is introduced into the ball mill jar to prevent the powder material from being oxidized during the grinding process.

[0119] (3) Set the rotation speed (800 rpm) and grinding time (25 hours), and run intermittently to avoid overheating.

[0120] (4) After grinding, the grinding balls are separated by sieving, and the nano powder is sieved at the same time (sieve aperture 60nm) to obtain pretreated nano-level additive A.

[0121] 2. Lead paste preparation process

[0122] Add 1000 parts lead powder, 8 parts sodium perborate, 1.3 parts polyester fiber, and premixed additive A to the paste mixer and start the dry mixing machine for 5 minutes. Then, spray 25 parts sulfonated polyaniline binder into the agitated lead paste in the paste mixer over 5 minutes. Next, pour in 120 parts deionized water over 3 minutes, and continue stirring for 5 minutes after the addition is complete. Then, pour in 100 parts dilute sulfuric acid over 9 minutes, and continue stirring for 13 minutes after the addition is complete. Stop the machine when the temperature drops below 45 degrees Celsius.

[0123] 3. The electrode plate adopts high-temperature curing technology. The high-temperature curing stage is at 78℃ for 9 hours and 93%RH. This ensures that sodium perborate decomposes when heated to produce oxygen, which promotes grid oxidation and further oxidation of free lead in lead paste.

[0124] Comparative Example 4

[0125] 1. Nano-scale pretreatment of additive component A:

[0126] (1) Add 70 parts of red lead powder, 35 parts of 4BS seed crystals and 10 parts of SnO2-rare earth mixture into a high-energy ball mill. Load hard grinding balls (zirconia and tungsten carbide in a mass ratio of 1:1) into the ball mill jar. The mass ratio of the added powder to the hard grinding balls is 1:10.

[0127] (2) Inert gas—argon—is introduced into the ball mill jar to prevent the powder material from being oxidized during the grinding process.

[0128] (3) Set the rotation speed (800 rpm) and grinding time (25 hours), and run intermittently to avoid overheating.

[0129] (4) After grinding, the grinding balls are separated by sieving, and the nano powder is sieved at the same time (sieve aperture 60nm) to obtain pretreated nano-level additive A.

[0130] 2. Additive B component water emulsification treatment

[0131] Add 30 parts of composite carbon material (carbon nanotubes: graphene: expanded graphite mass ratio = 1:2:3) and 40 parts of deionized water into an ultrasonic emulsifier. Stir at low speed for 30 minutes to fully wet the material. Then increase the shear speed of the emulsifier to 2800 r / min and emulsify for 50 minutes to obtain emulsion B.

[0132] 3. Lead paste preparation process

[0133] Add 1000 parts lead powder, 8 parts sodium perborate, 1.3 parts polyester fiber, and premixed additive A to the paste mixer and start the dry mixing machine for 5 minutes. Then, spray the pretreated additive component B into the agitated lead paste in the paste mixer over 5 minutes. Next, pour in 80 parts deionized water over 3 minutes, and continue stirring for 5 minutes after the addition is complete. Then, pour in 100 parts dilute sulfuric acid over 9 minutes, and continue stirring for 13 minutes after the addition is complete. Stop the machine when the temperature drops below 45 degrees Celsius.

[0134] 4. The electrode plate adopts high-temperature curing technology. The high-temperature curing stage is at 78℃ for 9 hours and 93%RH. This ensures that sodium perborate decomposes when heated to produce oxygen, which promotes grid oxidation and further oxidation of free lead in lead paste.

[0135] Detection Example 1

[0136] Positive electrode plates were prepared using the positive electrode lead paste from each embodiment and comparative example, and assembled into 6-DZF-20 batteries. The test results are shown in Table 1.

[0137] (1) 2h rate discharge (room temperature capacity): According to Clause 5.5 of the national standard GB / T22199-2017 for batteries, after the battery is fully charged, it is left to stand for 1 to 24 hours in an environment with a temperature of 25±2℃. When the battery voltage is 10.5V, the 2h rate capacity Ca should reach the C2 standard within three cycles.

[0138] (2) Cycle life: According to Clause 5.12 of the national standard GB / T22199-2017 for batteries, in an environment with a temperature of 25±5℃, discharge at a current of 10A for 1.6h, and then charge at a constant voltage of 16V (current limited to 4A) for 6.4h, which is one cycle. When the battery terminal voltage drops below 10.5V for three consecutive times after discharging for 1.6h, the battery cycle life ends. The total cycle life shall not be less than 350 cycles.

[0139] Table 1

[0140] Test sample Normal temperature capacity / Ah Cycle number / time Battery weight / kg Specific energy / (wh / kg) Example 1 21.8 410 6.05 43.24 Example 2 21.9 411 6.06 43.37 Example 3 22.1 413 6.05 43.83 Example 4 22.2 426 6.06 43.96 Example 5 22.9 438 6.06 45.34 Comparative Example 1 20.1 360 6.05 39.87 Comparative Example 2 21.9 412 6.05 43.44 Comparative Example 3 21.6 406 6.06 42.77 Comparative Example 4 21.7 418 6.05 43.04

[0141] The data above shows that adding quaternary carbon materials (carbon nanotubes, graphene, expanded graphite, and sulfonated polyaniline) can promote capacity and lifetime improvement. Adding rare earth element-SnO2 can prevent the active material from agglomerating or detaching during cycling, maintaining the porous structure of the electrode and improving charging efficiency. Changes in the ratio of rare earth elements to SnO2, within a certain range, have no significant impact on performance. Adding a mixture of quaternary carbon materials and rare earth-SnO2 can increase specific energy by 10%, lifetime by 20%, and capacity by 10%.

Claims

1. A rare earth-carbon-based composite lead-acid battery cathode additive formulation, characterized in that, By weight, it includes: 25-35 parts of carbon material, wherein the carbon material includes carbon nanotubes, graphene and expanded graphite; 20-30 parts of adhesive; 8 to 12 parts of SnO2-rare earth mixture, wherein rare earth includes Ce element, and the molar ratio of Ce element to Sn element is 1:8 to 10; 30-40 parts of 4BS seed crystals; 50-80 parts of nano red lead powder; 1 to 1.5 parts polyester fiber; Sodium perborate, 5-10 parts.

2. The rare earth-carbon based composite lead-acid battery cathode additive formulation according to claim 1, characterized in that, The adhesive is sulfonated polyaniline.

3. The rare earth-carbon based composite lead-acid battery cathode additive formulation according to claim 1, characterized in that, The mass ratio of the carbon nanotubes, graphene, and expanded graphite is 1:2:

3.

4. A method for preparing lead paste for the positive electrode of a lead-acid battery, characterized in that, The raw materials for preparing lead-acid battery positive electrode lead paste include lead powder, dilute sulfuric acid, water, and each material in the rare earth-carbon based composite lead-acid battery positive electrode additive formulation according to any one of claims 1 to 3; The mass ratio of lead powder and carbon material in the rare earth-carbon-based composite lead-acid battery cathode additive formulation is 1000:25-35; The preparation method includes the following steps: (1) The red lead powder, 4BS seed crystals and SnO2-rare earth mixture of the formula amount were ball-milled and mixed in an inert gas atmosphere, and the nano-sized powder was obtained by sieving to prepare pre-additive A. (2) Mix and emulsify the carbon material, binder and water in the specified amounts to obtain emulsion B; (3) Dry mix the lead powder, sodium perborate, polyester fiber and pre-made additive A according to the formula, then add emulsion B and water, mix evenly, then add dilute sulfuric acid, mix evenly and then make paste.

5. The method for preparing lead paste for the positive electrode of a lead-acid battery according to claim 4, characterized in that, In the raw materials for preparing the positive electrode lead paste for lead-acid batteries, by mass, every 1000 parts of lead powder corresponds to 90-105 parts of dilute sulfuric acid, and every 1000 parts of lead powder corresponds to 110-130 parts of water.

6. The method for preparing lead paste for the positive electrode of a lead-acid battery according to claim 4, characterized in that, In step (1), the ball milling is carried out in a ball mill, and hard grinding balls are also added to the ball mill. The mass ratio of the hard grinding balls to the added raw materials is 10:

1. The ball mill rotates at 500-1000 rpm, and the milling time is 20-30 hours. The sieve used for sieving has an aperture of 60 nm.

7. The method for preparing lead paste for the positive electrode of a lead-acid battery according to claim 4, characterized in that, In step (2), an ultrasonic emulsifier is used for mixing and emulsification. The shearing speed of the ultrasonic emulsifier during mixing and emulsification is 2500-3000 r / min, and the mixing and emulsification time is 45-60 min.

8. The method for preparing lead paste for the positive electrode of a lead-acid battery according to claim 4, characterized in that, In step (3), the temperature of the ointment should not exceed 45℃.

9. A lead paste for the positive electrode of a lead-acid battery, characterized in that, It is prepared using the method for preparing lead-acid battery positive electrode paste according to any one of claims 3 to 8.

10. A lead-acid battery, comprising a positive electrode plate, characterized in that, The positive electrode plate is prepared by coating the positive electrode lead paste of the lead-acid battery as described in claim 9 onto the positive electrode plate grid and then curing it at high temperature. The high temperature curing temperature is 75-80°C, the time is 8-10 hours, and the ambient humidity is controlled within the range of 90%-95% relative humidity.

Citation Information

Patent Citations

  • Lead plaster formula of positive plate of lead storage battery

    CN111509220A

  • Formula and preparation method of positive lead paste of deep circulation type lead-acid storage battery

    CN113675380A

  • Positive lead paste of lead storage battery and preparation method of positive lead paste

    CN117855467A

  • Positive electrode lead paste for storage battery with high capacity and long service life and preparation method of positive electrode lead paste

    CN118472190A

  • Positive electrode lead paste for long-life silicon-based bipolar lead battery and preparation method thereof

    US20240304807A1